Endotoxin, cytokines, and endotoxin binding proteins in obstructive jaundice and after preoperative biliary drainage - Kimmings, A (2000)
BACKGROUND—Obstructive jaundice is associated with postoperative complications related to increased endotoxaemia and the inflammatory response. In animals obstructive jaundice is associated with endotoxaemia and cytokine induction, which are reversed by internal biliary drainage. AIMS—To study endotoxaemia and the subsequent inflammatory response in obstructive jaundiced patients and after endoscopic biliary drainage. METHODS—In 15 patients with malignant distal obstructive jaundice, inflammatory and bacteriological parameters were assessed before endoscopic stent placement and after three weeks endoscopic drainage. RESULTS—Drainage reduced bilirubin from 252.5 to 45.1 µmol/l. At baseline low level endotoxaemia was detected (4.3 pg/ml) which was not affected after drainage (4.5 pg/ml). Serum interleukin 8 (IL-8) and endotoxin binding proteins were increased in jaundice and reduced after drainage (IL-8 113.6 to 20.7 pg/ml; lipopolysaccharide binding protein 24.2 to 16.5 µg/ml; sCD14 17.4 to 7.6 µg/ml; bactericidal/permeability increasing protein 2.9 to 1.8 ng/ml). Levels of other cytokines, augmented in animals, were only slightly increased and not changed after drainage (tumour necrosis factor (TNF): 21.7 and 18.4 pg/ml; sTNFr p55/75: 2.9/7.0 and 2.7/5.6 ng/ml; IL-6: 4.2 and 6.1 pg/ml; IL-10: 4.5 and 2.7 pg/ml). Elastase and lactoferrin tended towards reduction after drainage. All bile cultures were positive after stenting. CONCLUSIONS—The effects of obstructive jaundice in humans on endotoxin and cytokines are different from those in animal models. Obstructive jaundice causes alterations in circulating endotoxin binding proteins and IL-8. Concentrations of other mediators (TNF, previously suggested as being responsible for systemic endotoxaemia effects) are low and not affected by drainage.   Keywords: endotoxin; obstructive jaundice; cytokines; endotoxin binding proteins